The Dubai Incident - 1910 "Historical Study in Light of British Documents" - Al Omari , Thabet (Dirasat: Human and Social Sciences, 2022)
The present study aims at investigating the incident of Dubai which took place on 24/10/1910. This incident was caused by British officers and soldiers who searched two houses owned by Thani bin Khalifah and Ahmed bin Dalmuk. The search revealed some weapons and ammunition which were located beneath the one house. An armed struggle between the two parties occurred; four Britons and thirty-seven local citizens were killed. Accordingly, the British Government in the Persian Gulf region held Shaikh Butti bin Suheil responsible for the incident and sent him an ultimatum including several demands to be fulfilled within 48 hours; the most important of which was erecting a tide pole in the Dubai port, a fine payment of 50 thousand Rupees, handing over 400 rifles, establishing a post office and a telegraph station, and finally accepting the appointment of a British Political Agent in Dubai. The study concludes that the British officials utilized the incident to give privilege to the British Government to take control over the Emirate of Dubai and the adjacent Emirate of the Coastline despite the fact that Shaikh Butti bin Suheil had already accepted the conditions of the ultimatum and started implementing most of it.